Peritoneal tuberculosis as a cause of ascites in a patient with cirrhosis - Vaz, Ana Margarida (BMJ Case Rep, 2017)
A 59-year-old Portuguese Caucasian man with a history of heavy alcohol intake and no significant medical history presented with ascites, weight loss and general malaise. The ascitic fluid analysis showed 921 cells/mm(3) with mononuclear predominance (93.6%), elevated total proteins and a slightly elevated serum-ascites albumin gradient. The abdominal ultrasound confirmed the presence of chronic liver disease with ascites, and additionally on CT there was evidence of peritoneal thickening. On repeat paracentesis, the ascitic fluid analysis showed elevated adenosine deaminase but it was negative for the presence of mycobacteria by Ziehl-Neelsen stain, Löwenstein-Jensen culture and PCR amplification. Due to the persistent suspicion of tuberculosis, a laparoscopy was performed showing multiple small white tubercles scattered over the peritoneum. Peritoneal biopsies showed the presence of necrotising granulomas and cultures were positive for Mycobacterium tuberculosis complex. After a 6-month course of tuberculostatics, the ascites resolved completely. The patient remained asymptomatic.